Effects of Nigericin and Monactin on Cation Permeability of Streptococcus faecalis and Metabolic Capacities of Potassium-depleted Cells - Harold, F. M. (1968)
At a concentration of 10(−6)m, nigericin and monactin inhibited growth of Streptococcus faecalis, and the inhibition was reversed by addition of excess K(+). In the presence of certain antibiotics, the cells exhibited increased permeability to certain cations; internal Rb(+) was rapidly lost by exchange with external H(+), K(+) Rb(+), and, more slowly, with Na(+) and Li(+). No effect was observed on the penetration of other small molecules. Cation exchanges induced by nigericin and monactin were metabolically passive and apparently did not involve the energy-dependent K(+) pump. When the cells were washed, the cytoplasmic membrane recovered its original impermeability to cations. By use of monactin, we prepared cells whose K(+) content had been completely replaced by other cations, and the metabolic characteristics of K(+)-depleted cells were studied. Cells containing only Na(+) glycolyzed almost as well as did normal ones and, under proper conditions, could accumulate amino acids and orthophosphate. These cells also incorporated (14)C-uracil into ribonucleic acid but incorporation of (14)C-leucine into protein was strictly dependent upon the addition of K(+). When K(+) or Rb(+) was added to sodium-loaded cells undergoing glycolysis, these ions were accumulated by stoichiometric exchange for Na(+). From concurrent measurements of the rate of glycolysis, it was calculated that one mole-pair of cations was exchanged for each mole of adenosine triphosphate produced.